Characterization and expression of a spliced leader RNA in the parasitic nematode Ascaris lumbricoides var. suum. - Nilsen, T W (1989)
The parasitic nematode Ascaris spp. contains a 22-nucleotide spliced-leader (SL) sequence identical to the trans-SL previously described in Caenorhabditis elegans and other nematodes. The SL comprises the first 22 nucleotides of a approximately 110-base RNA and is transcribed by RNA polymerase II. The SL RNA contains a trimethylguanosine cap and a consensus Sm binding site. Furthermore, the Ascaris SL RNA has the potential to adopt a secondary structure which is nearly identical to potential secondary structures of similar SL RNAs in C. elegans and Brugia malayi.